2010
DOI: 10.1038/ki.2009.551
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency and anemia in early chronic kidney disease

Abstract: Vitamin D has a number of pleiotropic effects in a variety of tissues, in addition to its well-known effects on mineral metabolism. To determine whether it has an effect on erythropoiesis, we studied the association of the components of the vitamin D axis with the prevalence and severity of anemia in chronic kidney disease. We measured the concentrations of 25-hydroxyvitamin D (25D), 1,25-dihydroxyvitamin D (1,25D), and hemoglobin in a cross-sectional study of 1661 subjects in SEEK, a multi-center cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 29 publications
(38 reference statements)
7
91
1
2
Order By: Relevance
“…According to the results of this work, Patel et al [13] studied 1661 patients with renal disease. Levels of 25(OH)D and 1.25(OH) 2 D of these patients were independently correlated with decreased levels of hemoglobin and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this work, Patel et al [13] studied 1661 patients with renal disease. Levels of 25(OH)D and 1.25(OH) 2 D of these patients were independently correlated with decreased levels of hemoglobin and anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Infants' Hb level, serum Fe as well as 25(OH)D concentrations were increased after they were treated with intramuscular iron dextran (13) . Studies on patients with chronic kidney disease have also supported this association (14,15) .…”
mentioning
confidence: 88%
“…6 A reduction in ESA dose has been found in nonrandomized trials of nutritional vitamin D supplementation in patients on hemodialysis, [6][7][8] and cross-sectional studies show an inverse relationship between serum 25(OH)D and hemoglobin and ESA dose. [9][10][11][12] In vitro and in vivo studies under conditions of vitamin D deficiency have demonstrated increased erythropoeisis with addition of vitamin D. 13,14 The postulated mechanism for nutritional vitamin D's effect is via the suppression of cytokines inhibitory to erythroid progenitors. 14 Increased availability of iron through suppression of hepcidin may also play a role.…”
mentioning
confidence: 99%